The case of Argentina - Campana, Maximiliano Nicolás (2021)
In Argentina, the debate on the decriminalization and legalization of abortion reached its highest point in 2018 and spearheaded the reorganization of conservative religious and secular forces. These groups have been very active and achieved their goals: the law reform project was rejected by a very small number of votes. After this legislative rejection, a crusade against “gender ideology” erupted in the country. In the previous twelve years, the Kirchner administrations had taken important steps towards the recognition of sexual and reproductive rights and the implementation of public policies to guarantee them: the Sexual Health and Responsible Procreation laws, which established the free distribution of contraceptives (2002) and regulated assisted reproduction, the Comprehensive Sexual Education Law (2006), the Equal Marriage legislation (2010) and the Gender Identity Law (2012)...